Aktivitas Fisiologis Cincau Hijau Perdu (Premna oblongifolia) pada Pemberian Mikoriza dan Biochar Serat Aren: Physiological Activity of Green Grass Jelly Shrub (Premna oblongifolia) to Mycorrhiza and Palm Fiber Biochar Application - Arniputri, Retna Bandriyati; Rissa Kurnia Anggraini; Muji Rahayu; Djoko Purnomo (Jurnal Hortikultura Indonesia (JHI), 2025)
Green grass jelly shrub is a plant that has various benefits, so market demand for this plant continues to increase every year. On the other hand, the production of green grass jelly shrub has decreased so the market demand for this plant cannot be met. This study aims to determine the interaction between the dose of mycorrhiza and palm fiber biochar composition on the physiological activity of green grass jelly shrubs. Research with experimental methods was conducted in Greenhouse, Faculty of Agriculture, Universitas Sebelas Maret, June-October 2023. The method used was a two-factor randomized complete block design (RCBD) and 3 replicates. The first factor was the dose of mycorrhizal fertilizer (0, 5, 10, and 15 g plant-1) and the composition of planting media [soil (control), soil:palm fiber biochar (1:1), soil:palm fiber biochar (1:2), and soil:palm fiber biochar (2:1)]. Data experiments were analyzed using analysis of variance at the 5% error level and followed by Duncan’s Multiple Range Test at the 5% error level. The results showed that the dose of mycorrhiza 15 g plant-1 gave better results on plant height, weight of dry, number of stomata, and width of stomatal openings. Treatment of the composition planting media soil: palm fiber biochar with a ratio of 2:1 gave better results on stomatal opening width. Keywords: Phosphate, pectin, stomatal, transpiration, Verbenaceae